DETERMINAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN INDEKS LQ45 - Desmon Immanuel Paulus (2022)
This research is a quantitative research conducted to determine the determinants of financial performance on firm value in LQ 45 index companies listed on the IDX in a row from 2018-2020. The data used in this research is obtained from the company's annual report data that has been audited and published. This study uses 25 LQ 45 index companies as research samples with purposive sampling method. To analyze the data, this study uses a regression model selection test, panel data regression, partial hypothesis testing (t test) and R2 test using the Eviews 12 program. The results of these tests are known that (1) liquidity has no effect on firm value, (2) profitability has a positive and significant effect on firm value, (3) solvency has no effect on firm value